APPLICATION OF DYNAMIC VENTILATION STRATEGY TO IMPROVE ENERGY EFFICIENCY OF VENTILATION SYSTEMS - Levin, L.Yu.; Zaitsev, A.V.; Maltsev, S.V.; Kuzminykh , E.G. (Perm Federal Research Centre Journal, 2024)
Most mining companies have been mining mineral deposits since the second half of the 20th century. During this time, the length and branching of mines has grown substantially, with the total length of mine workings in some mines reaching 400 km. In such a situation, ventilation systems have become incredibly complex, involving simultaneous operation of up to 5 main fan units. Existing ventilation systems operate in a constant ventilation mode, that is maximum air is supplied to all working areas, regardless of the type of work. In addition, current methods for calculating the required amount of air for ventilation of working zones and the mine as a whole do not provide for dynamic control of air flows depending on the technological operations performed. The construction of automatic systems for calculating the required amount of air for mine ventilation, as well as dynamic control of air flows, will optimize the process of mine ventilation in accordance with the actual need for fresh air at the working areas and the mine as a whole when performing the relevant technological operations. The implementation of the dynamic ventilation strategy will significantly improve the energy efficiency of the ventilation system of both the existing and the projected mine. Moreover, the introduction of means for controlling the parameters of the mine atmosphere will make it possible to promptly respond to exceeding the maximum permissible concentrations of explosive and poisonous gases by increasing the air supply to the mining area. Thus, the application of dynamic ventilation strategy allows to obtain additional air reserve while improving aerological safety